Focal Microscopy Observe the Mechanism of Gegen Qinlian Decoction Treating Type 2 Diabetic Nephropathy in Nude Mice. - Zheng, Fei; Xu, Juan; Gu, Hao (BioMed Research International, 2022)
The incidence of diabetes is increasing year by year; among them, the rising trend of T2D is particularly obvious, and because it has many complications and poor prognosis, it has become one of the diseases that seriously endanger human health. Gegen Qinlian Decoction (GQD) has achieved good results in the treatment of type 2 diabetes (T2D). It can not only improve the anti-insulin effect of nude mice with type 2 diabetic, but also has the characteristics of small side effects and remarkable curative effect; it can improve the function of tissues and organs by multiple target spots and multiple ways. The method was to raise 30 nude mice with high fat and high sugar and inject small doses of streptozotocin (STZ). The treated nude mice were randomly divided into rosiglitazone group, Gegen Qinlian group, and model group, normally rearing 10 nude mice as a control group. The model group and the blank group were treated with 0.9% sodium chloride solution at 10 mL/kg, and the rosiglitazone group was intragastric administration with 3 mg/kg rosiglitazone solution. The GQD group was treated with 18.2 g/kg GQD, once a day, and lasting for 4 weeks. Use blood glucose meter to detect the FBG content in nude mice, use the radioimmunoassay to detect the amount of FINS, and calculate HOMA-IR. Use immunoenzyme linked assay method to detect the level of serum inflammatory factors. The experimental results showed that compared with the model group, the FBG of the rosiglitazone group mice was significantly decreased; the levels of the rosiglitazone group and the Gegen Qinlian group were significantly lower. Therefore, it is concluded that GQD can treat T2D in nude mice.